Tetrairon(ii) extended metal atom chains as single-molecule magnets. Issue 22 (13th May 2021) - Nicolini, Alessio; Affronte, Marco; SantaLucia, Daniel J.; Borsari, Marco; Cahier, Benjamin; Caleffi, Matteo; Ranieri, Antonio; Berry, John F.; Cornia, Andrea
Abstract : The iron(ii )-based extended metal atom chains [Fe4 (tpda)3 X2 ] (X = Cl, Br) have a weakly magnetic ground state but display SMM properties, which are detectable even in zero DC field when X = Br. Abstract : Iron-based extended metal atom chains (EMACs) are potentially high-spin molecules with axial magnetic anisotropy and thus candidate single-molecule magnets (SMMs). We herein compare the tetrairon(ii ), halide-capped complexes [Fe4 (tpda)3 Cl2 ] (1Cl ) and [Fe4 (tpda)3 Br2 ] (1Br ), obtained by reacting iron(ii ) dihalides with [Fe2 (Mes)4 ] and N 2, N 6 -di(pyridin-2-yl)pyridine-2, 6-diamine (H2 tpda) in toluene, under strictly anhydrous and anaerobic conditions (HMes = mesitylene). Detailed structural, electrochemical and Mössbauer data are presented along with direct-current (DC) and alternating-current (AC) magnetic characterizations. DC measurements revealed similar static magnetic properties for the two derivatives, with χ M T at room temperature above that for independent spin carriers, but much lower at low temperature. The electronic structure of the iron(ii ) ions in each derivative was explored by ab initio (CASSCF-NEVPT2-SO) calculations, which showed that the main magnetic axis of all metals is directed close to the axis of the chain. The outer metals, Fe1 and Fe4, have an easy-axis magnetic anisotropy ( D = −11 to −19 cm −1, | E / D | = 0.05–0.18), while the internal metals, Fe2 and Fe3, possess weaker hard-axis anisotropy ( D = 8–10 cm −1, | E / D | = 0.06–0.21). These single-ion parameters were held constant in the fitting of DC magnetic data, which revealed ferromagnetic Fe1–Fe2 and Fe3–Fe4 interactions and antiferromagnetic Fe2–Fe3 coupling. The competition between super-exchange interactions and the large, noncollinear anisotropies at metal sites results in a weakly magnetic non-Kramers doublet ground state. This explains the SMM behavior displayed by both derivatives in the AC susceptibility data, with slow magnetic relaxation in 1Br being observable even in zero static field.